Prevalence and factors associated with depressive symptoms among patients with epilepsy in Ethiopia: a national-based systematic review and meta-analysis - Tadesse, Gebresilassie; Tinsae, Techilo; Nakie, Girum; Rtbey, Gidey; Andualem, Fantahun; Tadesse, Asnake; Melkam, Mamaru; Takelle, Girmaw Medfu; Fentahun, Setegn (Frontiers in Neurology, 2024)
Background Depression is a major public health problem and negatively affects the quality of life of patients with epilepsy. Despite multiple studies investigating the magnitude and predictors, the results have been inconsistent. Therefore, this study aimed to estimate the pooled prevalence and factors associated with depressive symptoms among patients with epilepsy in Ethiopia. Methods The primary articles were searched using databases like PubMed, Google Scholar, CINAHL, SCOPUS, EMBASE, and African Journal Online. A total of 10 primary articles that assessed the prevalence and factors associated with depressive symptoms among patients with epilepsy in Ethiopia were included. A Microsoft Excel spreadsheet was used to extract the data, which was then exported to Stata version 14 for further analysis. The statistical heterogeneity was evaluated using the I2 test. Due to heterogeneity, a random effect meta-analysis model was employed. Publication bias was checked through Egger’s weighted regression test and funnel plot. Results A total of 10 primary studies with 3,532 participants were included. The pooled prevalence of depressive symptoms among patients with epilepsy was found to be 41.69% (95% CI, 37.70, 45.68). The pooled prevalence of depressive symptoms was 48.61, 42.98, 40.68, 38.27, and 34.80% in Oromia, SNNPs, Amhara, Addis Ababa, and Tigray, respectively, based on a sub-group analysis per regional state. Perceived stigma (AOR = 3.30, 95% CI: 1.40, 7.80), seizure frequency (AOR = 3.81, 95% CI: 1.03, 14.09), and perceived stress (AOR = 4.6, 95% CI: 1.05, 20.06) were factors associated with depressive symptoms. Conclusion We found that depressive symptoms affects at least four out of ten patients with epilepsy, indicating an immense burden. Depressive symptoms were extremely prevalent in those who had high levels of stigma, a monthly seizure frequency of once or more, and perceived stress. Therefore, physicians should take extra precautions when treating patients with epilepsy who have certain conditions. Systematic review registration This study was registered according to The International Prospective Register of Systemic Review (PROSPERO) with the registration ID (CRD42023484308).